1985
DOI: 10.1099/00222615-20-2-169
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Plasmid-Borne Aminoglycoside-Resistance Determinants in Staphylococci

Abstract: SUMMARY. Aminoglycoside-resistance determinants in staphylococci are borne on conjugative and non-conjugative plasmids. The conjugative plasmids were found in methicillin-resistant strains of Staphylococcus aureus isolated recently in Darwin and Sydney, Australia and in Houston, Texas, USA. These plasmids and the class-2 conjugative plasmid reported by Archer and Johnston (1 983) had similar patterns of EcoR 1 restriction-endonuclease fragments, encoded resistance to gentamicin, kanamycin and neomycin, transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Examination of the plasmid profiles showed that although these MRSA strains are gentamicin resistant, they do not have the large gentamicin resistance plasmid usually present in the London and Australian isolates (Bradley et al 1985;Townsend et al 1985), suggesting that genes coding for aminoglycoside resistance are sited on the chromosome, as in some of the recent Dublin isolates (Cafferkey et at. 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the plasmid profiles showed that although these MRSA strains are gentamicin resistant, they do not have the large gentamicin resistance plasmid usually present in the London and Australian isolates (Bradley et al 1985;Townsend et al 1985), suggesting that genes coding for aminoglycoside resistance are sited on the chromosome, as in some of the recent Dublin isolates (Cafferkey et at. 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance in staphylococci can arise by chromosomally mediated mechanisms, such as methicillin resistance; by mutation, such as resistance to rifampin, streptomycin, or fusidic acid; or by the acquisition of extrachromosomal DNA (38,54,64 (24), pGO4 and pUW3626 of Cohen et al (10), and pWG613 of Townsend et al (68) all appear to be similar to pAM899-1.…”
Section: Resistance Mechanisms and Interspecies Gene Exchange In Stapmentioning
confidence: 99%
“…11). Transfer of some conjugative plasmids has not been detected under cultural conditions that favour phage-mediated conjugation (Townsend et al, 1985c(Townsend et al, , 1986, but in the case of plasmid pWG78 they appear to only inhibit transfer (Table 3, expts. 9, 11).…”
Section: Discussionmentioning
confidence: 99%
“…As described by Townsend et al (1985c and d); Sp** transductants were selected on BHIA containing 0-5% (w/v) Na citrate and 150 mg/1 Sp.…”
Section: Phage Propagation and Transductionmentioning
confidence: 99%
See 1 more Smart Citation